Does having vulnerable friends help vulnerable youth? The co-evolution of friendships, victimization, and depressive symptoms in Chinese adolescents' social networks - Qin Xingna; Laninga-Wijnen Lydia; Steglich Christian; Zhang Yunyun; Ren Ping; Veenstra Rene (Wiley, 2025)
This study examined whether having vulnerable friends helps or hurts victimized and depressed (i.e., vulnerable) adolescents and whether this depends on classroom supportive norms. Students (n = 1461, 46.7% girls, 93.4% Han nationality) were surveyed four times from seventh and eighth grade (M-age = 13 years) in 2015 and 2016 in Central China. Longitudinal social network analyses indicated that having vulnerable friends can both hurt and help vulnerable adolescents. Depressed adolescents with depressed friends increased in victimization over time. Victimized adolescents with victimized friends increased in victimization but decreased in depressive symptoms. These processes were most likely in classrooms with high supportive norms. Having friends and a supportive classroom may hurt vulnerable adolescents' social position but help victims' emotional development.